FAKTOR – FAKTOR KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS DI KPP SEMARANG BARAT (Students' Journal of Accounting and Banking, 2012)
The willingness of taxpayers to pay taxes is essential in the tax revenue. Cause of a lack of will among other things is a principles of taxation, namely that the results of indirect taxation enjoyed by the taxpayer. This research aims to find empirical evidence of factors that influence the willingness to pay taxes. Factors that influence the willingness to pay predictable taxes, are: awareness of tax paying, knowledge and understanding of tax laws, and a good perception of the effectiveness of the tax system.Research sample is the taxpayer who performs in KPP Pratama Semarang Barat. The research was conducted by distributing questionnaires to the respondents of the study. Statistical methods used to test variables is multiple linear regression study.Keywords: Willingness to Pay Taxes, Awareness of Tax Paying, Knowledge and Understanding of Tax Laws, and a Good Perception of the Effectiveness of the Tax System